"It is important that we also remain a person ourselves": A qualitative study about the role of healthcare and social welfare services by Dutch parents caring for a child with profound intellectual and multiple disabilities at home - Liesbeth Geuze; Samuel Schrevel; Anne Goossensen (Elsevier, 2023)
Background: Parenting a child with profound intellectual and multiple disabilities has great implications. Parents generally rely heavily on healthcare and social welfare services in caring for the child at home. Previous studies indicated mismatch between what parents need to preserve family and personal wellbeing and what is typically provided by services. This study focused on the role of healthcare and social welfare services in childcare and aims to contribute to understanding how parents perceive their interactions with service providers. Methods: We interviewed 25 Dutch parents who cared for their child at home. Data were analysed using Framework Method. Findings: Two overarching themes were found: "Being the lifeline" addressed that parents had central roles in fragmented services, and "Losing ownership" highlighted that parents were constrained in living life according to own beliefs and values while interacting with providers. Conclusions: Findings illuminated that many parents became overburdened and compromised heavily on agency over family thriving due to functioning of healthcare and social welfare services. Findings supported working with integrated family case managers, creating effective and proactive access to equipment and services, and enacting high quality facilities for help with childcare and respite. These are important conditions to enable parents to construct family life more autonomously and make their further contribution to society. This may also lead to improved connotations of dependence on healthcare and social welfare services.